Kepuasan Nasabah di Era Digital: Peran Digitalisasi, Kepercayaan dan Bukti Nyata - Agnes Victoria Puspitarani; Kristina Anindita Hayuningtias (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Based on the expanded SERVQUAL model, this study seeks to contribute to the conventional banking literature by analyzing the effect of digitalization, trust, and tangible as dimensions of service quality on customer satisfaction. The method used in this study is a quantitative method involving 111 respondents as a sample. Data were collected using a questionnaire distributed through Google form, and data analysis was performed by multiple linear regression with the help of SPSS software. Factor and regression analyses were applied to identify the factor structure and measure the impact of service quality dimensions-digitization, trust, and tangible-on customer satisfaction in conventional banking. This research is one of the few studies investigating the factors that drive customer satisfaction of conventional banks in Indonesia in the digital era. The findings of this study show that trust and tangible have a significant influence on customer satisfaction at BCA Semarang. Meanwhile, the digitalization factor does not have a significant effect on current customer satisfaction of BCA Semarang.